FRACTIONAL GENERALIZATION OF TEMPERATURE FIELD PROBLEM IN OLI STRATA - Garg, Mridula; Rao, Alka; Kalla, S. L. (Matematichki Bilten, 2006)
We deal with temperature field problem for fractional lumped radial formulation in oil strata. To solve the boundary value problem for the fractional heat equation the method of integral transforms, namely, Laplace and Hankel transforms together with the modified form of convolution theorem known as Efro’s theorem is used. Use of Caputo’s differintegration operator provides new integral form of the solution.